EFEKTIVITAS MEDIA FLASHCARD TERHADAP KEMAMPUAN KOGNITIF SISWA DALAM MATERI SEGI BANYAK MENGGUNAKAN MODEL PBL KELAS 4 SDIT GLOBAL INSAN MADANI - Azizah Zahra; Joko Soebagyo (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2025)
Analyzing the efficiency of using flashcard media on students' thinking skills related to the topic of polygons using the Problem-Based Learning (PBL) model in class IV SDIT Global Insan Madani. The basis of this study began with the low learning achievement of students in mathematics, especially in geometry material, due to monotonous teaching methods and minimal variation in learning media. The method applied in this study is the One Group Pretest-Posttest Design, involving 24 students as samples. The findings of the study indicate that the use of flashcard media in mathematics learning with the PBL approach can significantly improve students' cognitive abilities. Flashcards play a role in visualizing concepts and facilitating understanding of the material, while PBL increases students' active participation in solving problems. The combination of these two methods has proven effective in deepening understanding of the concept of polygons and increasing students' learning motivation. This study recommends the use of flashcard media as an innovation in teaching to improve mathematics learning outcomes at the elementary school level.